Shamakhi safari park eco-tourism potential: Biodiversity, sustainability, and climate monitoring (Zoo Botanica, 2025)
The investigation employs advanced remote sensing techniques to precisely delineate the geo-geographical characteristics of Shamakhi Safari Park, covering approximately 480 hectares within a larger 620-hectare forested landscape bounded. Located at 40°45′32.16″N and 48°32′26.52″E, high-resolution satellite imagery from Esri World Imagery and Maxar, with a spatial resolution of 0.46 meters and positional accuracy of 5 meters, facilitated detailed mapping of the park’s terrain, vegetation cover, and habitat diversity. The analysis identified heterogeneous topography comprising mountainous relief, dense oak and pine forests, steppe areas, and wetland ecosystems, which collectively contribute to the park’s rich biodiversity, including habitats for several protected and endemic species. Extending roughly 3.43 km in length, the park’s adjacency to Pirgulu State Preserve and historic villages enhances its ecological connectivity and cultural value, reinforcing its role as a significant eco-tourism hub. The study’s results provide a scientific foundation for sustainable tourism development and natural resource management by highlighting critical conservation areas, promoting habitat restoration, and encouraging local community involvement to ensure long-term ecological resilience. Finally, the aim of this study is to inform evidence-based strategies that balance ecological preservation with sustainable tourism growth, supporting both environmental integrity and socio-economic benefits for the region
Keywords: Shamakhi safari park; eco-tourism; biodiversity; sustainability; climate